Development of the traditional digital games for strengthening childhood's verbal skill - Nuur Wachid Abdul Majid; Taufik Ridwan (Jurnal Pendidikan Vokasi, 2019)
The aims of this research was to: (1) know the portability aspect of the Traditional Digital Games application as a medium for early childhood learning; and (2) know the usability aspect of the Traditional Digital Games applications as a medium for early childhood learning. The method used in this study is Research and Development (R & D). The stages through which the waterfall will be useful to be able to produce reliable and effective software. The waterfall flowchart consists of: analysis, design, implementation, testing, and improvement. The results of this study were: (1) the results of testing from the portability aspect using a different smartphone, it can be concluded that traditional digital game applications have entered into a very good category; and (2) the results of testing usability aspects averaged over 70%, so that in both aspects the test was considered feasible and good. Although in the aspect of learning games the score shows 70.83% so it needs an increase.